An Explicit MOT-TDVIE Scheme for Analyzing Electromagnetic Field Interactions on Nonlinear Scatterers - Ulku, H. Arda; Bin Sayed, Sadeed; Bagei, Hakan (IEEE, 2015)
An explicit marching on-in-time (MOT) based time domain electric field volume integral equation (TDVIE) solver for characterizing electromagnetic wave interactions on scatterers with nonlinear material properties is proposed. Discretization of the unknown electric field intensity and flux density is carried out by half and full Schaubert-Wilton-Glisson basis functions, respectively. Coupled system of spatially discretized TDVIE and the nonlinear constitutive relation between the field intensity and the flux density is integrated in time to compute the samples of the unknowns. An explicit PE(CE)(m) scheme is used for this purpose. Explicitness allows for easy incorporation of the nonlinearity as a function only to be evaluated on the right hand side of the coupled system of equations. A numerical example that demonstrates the applicability of the proposed MOT scheme to analyzing electromagnetic interactions on Kerr-nonlinear scatterers is presented.
IEEE International Conference on Computational Electromagnetics (ICCEM) -- FEB 02-05, 2015 -- City University of Hong Kong, Kowloon Tong, HONG KONG
Keywords: marching on-in-time (MOT); transient analysis; explicit solver; volume integral eqaution; Kerr nonlinearity